Complete Basic Immunization of Children 12-23 Months Based on Geographical Differences and Determinants of Utilization - Ayun Sriatmi; Martini Martini; Sutopo Patria Jati; Novia Handayani; Aditya Kusumawati; Armunanto Armunanto (Al-Sihah : The Public Health Science Journal, 2023)
Although immunization has been proven to be cost-effective in preventing dangerous infectious diseases, its complete utilization is not optimal. Therefore, this study aims to analyze the Complete Basic Immunization (CBI) coverage among children aged 12-23 months based on differences in geographical characteristics areas, and factors influencing its utilization. This was an analytic study conducted with a quantitative method and cross-sectional approach, and was carried out in 31 districts in Central Java Province, which were categorized into coastal and mountainous areas. The target population included all children aged 12-23 months, and a sample of 685 children was selected using a purposive sampling technique. The collected data were analyzed using independent t-test for numerical, and chi-square for categorical data. Based on the results, the CBI coverage did not differ between children living in coastal and mountainous areas, except for HB-0, BCG, and DPT/HB/HiB-1 immunizations which were significantly different. Furthermore, the mean score of attitudes, perceptions (about barriers, AEFI, multiple injections), information sources, motivation, and service satisfaction among children living in coastal areas were higher and proved to be significantly different from those living in mountainous areas. Access to healthcare facilities and their availability also emerged as a differentiating factor between the two areas. To improve CBI utilization, effective strategies include using appropriate communication, information, and socialization media, particularly through internet technology. These strategies should be integrated into Information, Education, and Communication (IEC) program, alongside improving access and immunization service systems.